Thesis Quality of Primary School Teacher Education Department - Ramdhan Witarsa; Moh. Fauziddin; Zuwati Hasim; Lussy Midani Rizki (Graduate School of Universitas Negeri Malang, 2022)
Abstract: This study aims to describe the quality of students' thesis in the primary school teacher education study program. The method used in this research is descriptive qualitative case study. This method has three stages, namely: the description stage, the reduction stage, and the selection stage. The data in this study were sourced from 16 students graduating in 2020 and 2021 at one of the private universities in Riau. The results of this study can show that the quality of student thesis is stagnant and tends to decrease in quality. Therefore, this research can be used as a reference in improving the lecture process and the mentoring process in the next academic year.